Critical Analysis of Collaborative Practices, Patient Outcomes, And Technological Use in Respiratory Therapy and Nursing - Busuhail, Hassan Yousef; almaghrabi, Omar Mohammed; Almuntashiri, Abdulrahman Ali; Banakhr, Feras Ali; Sharahili, Mohammed Ahmed; Marran, Asim Khalil; Alharbi, Moath Abdullah; Alsulami, Sultan Nawar; Al-Saadi, Mishaal Radah; Al-Shahri, Fatima Gharman (Journal of Ecohumanism, 2024)
Respiratory therapy and nursing are strong dating as patient care in healthcare settings, especially in acute and intensified care facilities, including ICU, emergency, and pulmonary rehabilitation. Due to respiratory illnesses, RT and nurses complement each other in providing patient care, effectiveness in clinical processes, and article improvement. Also, the nursing practice and respiratory therapy have seen the use of technology improve treatment, monitoring, and patient education. This paper will critically evaluate the working relationships between respiratory therapists and nurses, analyze the efficiency of interventions by these professionals, and focus on the issues of technology utilization in both professions. By considering the major topics like the profession and responsibilities of both rt and nursing, the relationship between both occupations, and the role of technology and patient-focused care, this paper also intends to review how rt and nursing enhance the quality of the outcome of the health care system.